Nosocomial outbreak of hepatitis B virus infection in a pediatric hematology and oncology unit in South Africa: Epidemiological investigation and measures to prevent further transmission. Issue 11 (5th June 2015) - Büchner, Ané; Du Plessis, Nicolette M.; Reynders, David T.; Omar, Fareed E.; Mayaphi, Simnikiwe H.; Haeri Mazanderani, Ahmad F.; Avenant, Theunis
<x xml:space="preserve">Abstract</x> Background Hospital‐acquired hepatitis B virus (HBV) infection has been well described and continues to occur worldwide. Recent nosocomial outbreaks have been linked to unsafe injection practices, use of multi‐dose vials, and poor staff compliance with standard precautions. This report describes a nosocomial outbreak that occurred in a pediatric hematology and oncology unit of a large academic hospital, the epidemiological investigation of the outbreak, and preventive measures implemented to limit further in‐hospital transmission. Methods Outbreak investigation including contact tracing and HBV screening were initially carried out on all patients seen by the unit during the same period as the first three cases. Routine screening for the entire patient population of the unit was initiated in February 2013 when it was realized that numerous patients may have been exposed. Results Forty‐nine cases of HBV infection were confirmed in 408 patients tested between July 2011 and October 2013. Phylogenetic analysis of the HBV preC/C gene nucleotide sequences revealed that all tested outbreak strains clustered together. Most (67%) patients were HBeAg positive. The cause of transmission could not be established. Preventive measures targeted three proposed routes. HBV screening and vaccination protocols were started in the unit. Conclusions The high number of HBeAg positive patients, together with suspected lapses in infection prevention and control measures, are believed to have played a major role in the transmission. Measures implemented to prevent further in‐hospital transmission were successful. On‐going HBV screening and vaccination programs in pediatric hematology and oncology units should become standard of care. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.